2018
DOI: 10.3390/su10114076
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Congruency between Ideal Self and Brand Image on Sustainable Happiness

Abstract: Building on the Sustainable Happiness Model, this study examines how congruency between ideal self-concepts and brand image influences a sense of happiness. The findings show that when the ideal self-image and the ideal social self-image are congruent with brand image, a sense of happiness can be enhanced through brand identification and positive emotions. An additional two-mediation analysis confirms that there are full mediation effects of brand identification and positive emotions between ideal self/ideal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(56 reference statements)
1
0
0
Order By: Relevance
“…Consequently, it is necessary to better understand the role of the shopping environment in influencing the well-being of online consumers. Furthermore, our findings are consistent with previous studies, which confirmed the relationship between social presence and shopping enjoyment and the association between shopping enjoyment and consumer well-being [105,106].…”
Section: Theoretical Contributionssupporting
confidence: 93%
“…Consequently, it is necessary to better understand the role of the shopping environment in influencing the well-being of online consumers. Furthermore, our findings are consistent with previous studies, which confirmed the relationship between social presence and shopping enjoyment and the association between shopping enjoyment and consumer well-being [105,106].…”
Section: Theoretical Contributionssupporting
confidence: 93%
“…The self-congruity theory indicates that an individual's perceived match between his/her self-concept and a product's/brand's attributes is likely to affect his/her attitudes and behaviors related to that product/brand [34]. A number of previous studies have drawn the conclusion that the relationship between consumers' self-concept and a brand's image (i.e., self-brand image congruency) is positively correlated with the brand attitude, intention, and behavior [18,35,36]. Likewise, many tourism studies have also applied the self-congruity theory to the destination context and discovered that a good congruity between a tourist's and a destination's image (i.e., self-destination image congruency) would positively affect his/her attitudes and behaviors toward that destination [13,[37][38][39][40].…”
Section: Self-destination Personality Fit As a Moderatormentioning
confidence: 99%